Crowding as a primary source of stress in an endangered fragment‐dwelling strepsirrhine primate. (19th October 2017) - Gabriel, D. N.; Gould, L.; Cook, S.
Abstract: Nutritional and social challenges arising from habitat fragmentation can be significant sources of stress for animals. If prolonged, such stressors can pose a threat to the longevity of a species within a fragmented landscape. While each may elicit a physiological response, the coupled and often additive nature of these stressors can make it difficult to determine their relative impact on an individual or population. We measured fecal glucocorticoids (fGC) in two populations of Lemur catta, an endangered strepsirrhine primate, inhabiting forest fragments that vary markedly in resource structure and population density. We also examined the relative importance of behavioral variables indicative of feeding environment, intergroup territoriality, and intragroup social interactions in predicting fGC levels in these populations. Lemur catta living with ample food resources but at high population density exhibited higher fGC concentrations throughout the study period, independent of sex or reproductive state. At both sites, fGC levels reflected consistent seasonal variation, with lowest levels occurring during the resource‐rich pre‐mating period. Foraging effort was positively associated with fGC levels at each site, yet the population exhibiting the highest foraging effort had consistently lower levels of fGC. Intergroup territoriality was a positive predictor and intragroup agonism a negative predictor of fGC levels; however, trends in these variables were inconsistent when examining the two sites separately. Within‐site group differences highlighted the additive nature of nutritional and social stressors in predicting fGC levels. Our results suggest that the intense or unpredictable impact of crowding and, correspondingly, heightened intergroup resource defense may be an important consideration when addressing long‐term conservation initiatives for fragment‐dwelling L. catta . Abstract : To examine the challenges associated with nutritional and social stressors for fragment‐dwelling wildlife, we measured fecal glucocorticoids (fGC) in two populations of endangered Lemur catta inhabiting forest fragments that varied markedly in resource structure and population density. L. catta living with ample food resources but at high population density exhibited higher fGC concentrations throughout the study period, and overall, foraging effort and intergroup territoriality were positive predictors and intragroup agonism was a negative predictor of fGC levels. Our results suggest that the intense or unpredictable impact of crowding and, correspondingly, heightened intergroup resource defense may be an important consideration when addressing long‐term conservation initiatives for fragment‐dwelling L. catta .